(untitled) (Studies in Ancient Art and Civilisation, 2023)
The Jerash archaeological site holds great significance as one of the most prominent Roman sites in the Middle East. In our research paper, we present an assortment of marine shells discovered in the northern region of the Jerash archaeological site during the University of Jordan’s excavations from 2017 to 2019. We analyze the shells to determine their species. Additionally, we document the human modifications of the shells in order to reconstruct their possible use. The number of shells is small, but their value is heightened by the variety of species represented and the human modifications observed. The most frequently found shell are 12 murex (11 are Bolinus brandaris). Some shells exhibit perforations, which could be attributed to various purposes such as adornments, the production of cosmetics, or souvenirs.